Extracellular vesicles in reproductive medicine: from “animal-led” to “plant-enabled” - Pan, Keying; Ju, Wenhan; Wang, Yue; Zhang, Qianwen; Wang, Ruyi; Jiang, Xingyue; Zhao, Shuai (Frontiers in Cell and Developmental Biology, 2025)
Extracellular vesicles (EVs) have emerged as pivotal mediators of intercellular communication in reproductive medicine, demonstrating considerable potential for both understanding and treating reproductive disorders. By precisely regulating key processes such as follicular development, embryo implantation, and the immune microenvironment, EVs present innovative opportunities for the precision treatment of infertility. However, the clinical translation of conventional animal-derived EVs faces significant challenges, including inherent heterogeneity, difficulties in scalable production, and ethical concerns. These limitations have accelerated the exploration of sustainable and safer alternatives, notably plant-derived extracellular vesicles (PDEVs). This paradigm shift from animal to plant sources is paving the way for a new era of green precision medicine in EV-based therapies.